Analisis Kemampuan Berpikir Kreatif Peserta Didik dalam Kegiatan P5 Tema Gaya Hidup Berkelanjutan - Alda Risma; Afrom, Ichyatul (Sangkalemo : The Elementary School Teacher Education Journal, 2025)
This study aims to describe the creative thinking abilities of fifth-grade students at SDN 10 Langkai during the implementation of the Pancasila Student Profile Strengthening Project (P5) on the theme of Sustainable Lifestyle. The study was motivated by a learning approach that gives students the freedom to create their own projects without predetermined models from the teacher. This research employed a descriptive qualitative method involving three students, using observation, interviews, and product assessments based on four creative thinking indicators: fluency, flexibility, originality, and elaboration. The findings indicate that students demonstrated creative thinking skills categorized as "creative" with an average indicator score of 66,66. The creative products developed by the students received a score of 73,33 from external observers and 83,33 from the teacher. The study concludes that the P5 project activities are generally effective in developing students creative thinking abilities, although further guidance is still needed to strengthen all aspects of creativity.